2017
DOI: 10.1186/s12883-017-0913-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, safety and health-related quality of life of multiple sclerosis patients treated with fingolimod: results from a 12-month, real-world, observational PERFORMS study in the Middle East

Abstract: BackgroundEvidence on the use of fingolimod in real-world clinical practice and data on patient-reported health-related quality of life (HRQoL) in countries such as the Middle East are sparse. The Prospective Evaluation of Treatment with Fingolimod for Multiple Sclerosis (PERFORMS) study assessed HRQoL and effectiveness and safety of fingolimod in patients with relapsing-remitting multiples sclerosis (RRMS), primarily in Middle Eastern countries.MethodsThis 12-month, observational, multicentre, prospective, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
4
14
0
1
Order By: Relevance
“… 44 Reports from observational studies with an observational period of 12 months give AE incidence rates of 35% to 60%. 45 , 46 Noteworthy is that no participant reported any cardiovascular adverse event during the six-month study period. The proportion of relapse-free PwMS during the study period was about 90% in both groups.…”
Section: Discussionmentioning
confidence: 99%
“… 44 Reports from observational studies with an observational period of 12 months give AE incidence rates of 35% to 60%. 45 , 46 Noteworthy is that no participant reported any cardiovascular adverse event during the six-month study period. The proportion of relapse-free PwMS during the study period was about 90% in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Fingolimod (FNG), proven efficacious in three large phase III trials [1][2][3] and in their extensions [4,5], is a widely used oral medication licensed in the USA for the first-line treatment of relapsing-remitting form of multiple sclerosis (RRMS) and in the European Union (EU) for patients with highly active RRMS defined as either high disease activity despite treatment with at least one disease-modifying treatment (DMT) or rapidly evolving severe RRMS. A large number of postmarketing studies have confirmed the efficacy of FNG in a real-world setting, with data substantially overlapping those of pivotal trials [6][7][8][9][10][11][12][13]. All this despite patients are included in observational studies being on average older, with longer disease duration and more severe neurological disability [14].…”
Section: Introductionmentioning
confidence: 91%
“…There was, however, a slight improvement in the “psychological well-being subscore” for fingolimod-treated patients at months 6 and 12 ( P =0.002 and P <0.01 versus baseline, respectively). 50 …”
Section: Impact Of Fingolimod On Quality Of Life and Patient-reportedmentioning
confidence: 99%